Implementation of XFEM in the study of gear crack propagation behaviour using the SIF on different moments - Hiung, F.; Al-Qrimli, Haidar; Morris, K. (Inderscience Publishers, 2017)
Copyright © 2017 Inderscience Enterprises Ltd. The application of gears, especially spur gear, is widely available in most engineering applications. Especially for high module steel spur gear, it is used extensively in heavy machineries such as cranes and metal crushers. Therefore, it is crucial to avoid catastrophic damage to gears by understanding the crack behaviour. Provided the crack does not propagate into the rim, only minor accidents are likely to happen or else catastrophe may be expected again. Therefore, the study of crack behaviour on stress intensity factor (SIF) with different magnitude of moment was conducted. This study implemented the application of extended finite element method (XFEM) in ABAQUS to overcome the limitations of a conventional method, the finite element method (FEM). The need of re-meshing was avoided in this simulation. The crack propagation pathways were visualised using the 'STATUSXFEM'.